Prevalence and severity of alopecia lesions on gray bats, Myotis grisescens, peaks during lactation. - Ashleigh B Cable; Megan Kinsella; Richard Gerhold; Elizabeth Hamrick; Cory Holliday; Chris Ogle; Robert T Stinson Ii; Dustin Thames; Emma V Willcox (PLoS ONE)
We observed multiple gray bats (Myotis grisescens) in 2022 with large patches of fur loss (i.e., alopecia) on the dorsal surface of their body. Alopecia in wildlife has been linked to multiple possible factors and often is a sign of suboptimal health. In 2023, we designed an experiment to compare prevalence of alopecia in gray bats across various reproductive stages, characterize the severity of alopecia lesions, and determine the ectoparasites and microbiota present on the regions of fur loss. We harp-trapped four summer gray bat roosts 2-3 times between 11 April-30 August 2023 and collected skin swabs and scrapes from each bat with alopecia. We determined the severity of the alopecia lesions on a scale 0-7 by summing the degree of redness (0-2), skin condition (0-1), and percentage of fur loss (0-4). We cultured the skin swabs for fungal and bacterial growth and examined skin scrapes under a microscope to determine the presence of subcutaneous mites. We found no evidence that subcutaneous mites cause the fur loss. We determined that prevalence of alopecia in M. grisescens varies throughout the summer. Prevalence is highest for female bats that are or recently were lactating, reaching an average of 6% ± 6 SD (0-15% range) of captured females exhibiting fur loss during the pup rearing period. Alopecia is most prevalent in male bats in early summer (1% ± 2 SD; 0-4% range). Lactating females had more severe cases than males and were often associated with skin redness due to unknown causes. Bats with alopecia did not differ in body condition, determined from body mass, from bats without alopecia. Future studies could investigate the role of stress in possible autoimmune responses contributing to alopecia. Conservation strategies aimed at reducing stress and supporting nutritional requirements during the summer are likely beneficial to M. grisescens.